2011
DOI: 10.1029/2011jd016003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observations of the wind field in the Antarctic and Arctic mesosphere and lower-thermosphere at conjugate latitudes

Abstract: [1] Mean winds, semidiurnal and diurnal tides, and trends and long-period oscillations spanning a solar cycle (from early 1999 through June 2010) measured by medium frequency (MF) radars at conjugate Antarctic and Arctic latitudes (Syowa, Antarctica, 69°S, 39.6°E, and Andenes, Norway, 69.3°N, 16°E) are described and compared. Zonal mean winds are stronger and more uniform from year to year over the Antarctic, with a stronger eastward winter jet spanning the range of altitudes presented (70 to 96 km). The summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 122 publications
5
32
0
Order By: Relevance
“…In principle, given the mean zonal and meridional winds similarities described in the last paragraph and in previous studies [e.g., Iimura et al ., ; Fritts et al ., ], one would expect comparable characteristics between different hemisphere's tidal components. The analysis carried out in this study tells us that they are different though.…”
Section: Resultsmentioning
confidence: 98%
“…In principle, given the mean zonal and meridional winds similarities described in the last paragraph and in previous studies [e.g., Iimura et al ., ; Fritts et al ., ], one would expect comparable characteristics between different hemisphere's tidal components. The analysis carried out in this study tells us that they are different though.…”
Section: Resultsmentioning
confidence: 98%
“…Ground‐based studies of the mesosphere and lower thermosphere (MLT) have addressed interhemispheric differences in mean temperatures and winds, tides, planetary waves (PWs), gravity waves (GWs), and the constituent distributions and microphysical processes that depend on them from midlatitudes to polar latitudes [e.g., Vincent et al , 1988; Avery et al , 1989; Portnyagin et al , 1993a, 1993b, 2006; Fraser et al , 1995; Huaman and Balsley , 1999; Dowdy et al , 2001, 2007; Chu et al , 2003; Kishore et al , 2003; Riggin et al , 2003; Day and Mitchell , 2010a, 2010b; Iimura et al , 2011]. Similar studies employing satellite data have provided a more uniform global perspective for specific fields.…”
Section: Introductionmentioning
confidence: 99%
“…The MF radar has continuously operated at Syowa Station (69.0°S, 39.6°E) since March 1999, and it has provided horizontal wind at altitudes of 50−120 km in the mesosphere and lower thermosphere for approximately 17 years. Iimura et al (2011) reported seasonal variations and trends in the TWs observed at Syowa Station. Murphy et al (2007) examined the climatology of the PWs at Davis Station (68.3°S, 77.6°E) for three wave period ranges and discussed their differences.…”
Section: Introductionmentioning
confidence: 99%